Frizzled3 expression and colony development in hydractiniid hydrozoans. Issue 5 (8th July 2020) - Sanders, Steven M.; Travert, Matthew K.; Cartwright, Paulyn
Abstract: Hydractiniid hydrozoan colonies are comprised of individual polyps connected by tube‐like stolons or a sheet‐like mat. Mat and stolons function to integrate the colony through continuous epithelia and shared gastrovascular cavity. Although mechanisms of hydrozoan polyp development have been well studied, little is known about the signaling processes governing the patterning of colonies. Here we investigate the Wnt receptor family Frizzled. Phylogenetic analysis reveals that hydrozoans possess four Frizzled orthologs. We find that one of these genes, Frizzled3, shows a spatially restricted expression pattern in colony‐specific tissue in two hydractiniid hydrozoans, Hydractinia symbiolongicarpus and Podocoryna carnea, in a manner that corresponds to their distinct colony forms (stolonal mat in Hydractinia and free stolons in Podocoryna ). Interestingly, Frizzled3 was lost in the genome of Hydra, which is a solitary polyp and thus lacks colony‐specific tissue. Current evidence suggests that the Wnt signaling pathway plays a key role in the evolution of colony diversity and colony loss in Hydrozoa. Abstract : Frizzled3 expression in colony tissue of Hydractinia symbiolongicarpus . Research Highlights: Frizzled3 expression in two colonial hydrozoans is consistent with it playing a role in the development and patterning of colony‐specific tissues, implicating the Wnt signaling pathway in the evolution and development of hydrozoan colonies.